Structural features underlying raloxifene's biophysical interaction with bone matrix. Issue 4 (15th February 2016) - Bivi, Nicoletta; Hu, Haitao; Chavali, Balagopalakrishna; Chalmers, Michael J.; Reutter, Christopher T.; Durst, Gregory L.; Riley, Anna; Sato, Masahiko; Allen, Matthew R.; Burr, David B.; Dodge, Jeffrey A.
Graphical abstract: Abstract: Raloxifene, a selective estrogen receptor modulator (SERM), reduces fracture risk at least in part by improving the mechanical properties of bone in a cell- and estrogen receptor-independent manner. In this study, we determined that raloxifene directly interacts with the bone tissue. Through the use of multiple and complementary biophysical techniques including nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy (FTIR), we show that raloxifene interacts specifically with the organic component or the organic/mineral composite, and not with hydroxyapatite. Structure–activity studies reveal that the basic side chain of raloxifene is an instrumental determinant in the interaction with bone. Thus, truncation of portions of the side chain reduces bone binding and also diminishes the increase in mechanical properties. Our results support a model wherein the piperidine interacts with bone matrix through electrostatic interactions with the piperidine nitrogen and through hydrophobic interactions (van der Waals) with the aliphatic groups in the side chain and the benzothiophene core. Furthermore, in silico prediction of the potential binding sites on the surface of collagen revealed the presence of a groove with sufficient space to accommodate raloxifene analogs. The hydroxyl groups on the benzothiophene nucleus, which are necessary for binding of SERMs to the estrogen receptor, are not required for binding to the bone surface, but mediate a more robust binding of the compound to the bone powder. In conclusion, we report herein a novel property of raloxifene analogs that allows them to interact with the bone tissue through potential contacts with the organic matrix and in particular collagen.